Descriptive analyses of maternally-derived antibody levels against porcine circovirus 2 (PCV-2) in 3- and 21-day-old piglets from farms of four European countries using different vaccination protocols in sows - M. Sibila; A. Llorens; E. Huerta; C. Fablet; M. Faderl; L. Ferrari; N. Rose; A. Palzer; P. Martelli; M. C. Venegas-Vargas; D. Fredrickson; L. Taylor; et al. (Porcine Health Management, 2022)
Abstract Background Up to now, information on the levels of maternally-derived antibodies (MDA) against PCV-2 in suckling piglets born to sows vaccinated with different strategies is scarce in the literature. In the present observational study, the PCV-2-specific MDA titres from piglets from 109 farms (thirty 3-day-old and thirty 21-day-old piglets per farm) across four different European countries (France n = 30, Germany n = 27, Italy n = 22 and Spain n = 30) using different sow vaccination strategies (during gestation, as a gilt, as a piglet or never) were assessed. Results In all four countries, mean log PCV-2 MDA titres were higher in 3-day-old piglets than in the 3-week-old ones, being significant in most of all the comparisons performed. Within each country, the highest PCV-2-specific MDA titres were observed in the 3-day-old piglets born to sows vaccinated during gestation. Indeed, in the four countries, more than 60% of this subpopulation (3-day-old piglets from sows vaccinated during pregnancy) had the highest log PCV-2 titres detectable with the ELISA technique used in this study. The lowest MDA titres were more variable. Whereas in France and Germany the lowest titres corresponded to 21-day-old piglets born from sows vaccinated as a piglet, in Italy, they corresponded to 21-day-old piglets derived from sows vaccinated as a gilt and in Spain to 21-day-old piglets born from non-vaccinated sows. In this study, PCV-2-specific MDA titres at 3 and 21 days of age were not affected by sow parity. Conclusions Data obtained could be considered as a European global overview of PCV-2-specific MDA titres present in the pre-vaccinated piglet populations in different European countries, with titres tending to be higher in younger piglets, but with values variable among countries and sow vaccination strategies.